A new Korean species of Pararhabdepyris Gorbatovsky (Hymenoptera, Bethylidae) with an updated world key - Lim, Jongok; Kim, Il-Kwon (Zootaxa, 2024)
Pararhabdepyris Gorbatovsky is a small genus within Bethylidae, currently comprising only six valid species worldwide. A new species, Pararhabdepyris directus Lim sp. nov., is described and illustrated from South Korea. It appears closely related to P. paradoxus, is characterized by the combination of the following characters: the basal two-thirds of the scape are dark castaneous, coxa and femora are dark castaneous, the median and submedian areas of metapectal-propodeal disc are rugulose, and the transverse posterior carina of metapectal-propodeal complex is straight. An updated key to the world species of the genus are presented.